Reaksi Pasar Modal Terhadap Kasus Penyelundupan Harley Dan Brompton Melalui Garuda Indonesia (Event Study pada Saham BEI Sub Sektor Transportasi) - Sari, Jayanti Mekar; Julianto, I Putu (Universitas Pendidikan Ganesha, 2020)
The purpose of this study is to establish whether or not there is a stock market reaction using Average Abnormal Return dan Average Trading Volume Activity variables. This type of study is an Event Study. The population of this study is companies that leas in Indonesia Stock Exchange. Sampling technique used Sampling Total method, with number 42 companies. Data analysis that used are descriptive analysis test, normality test and hypothetical test (Paired Sample t-Test) with SPSS version 25.0.Â The result shows that there is no difference in Average Abnormal Return before and after smuggling cases of Harley and Brompton through Garuda Indonesia and there is no difference too in Average Trading Volume Activity before an after smuggling cases of Harley and Brompton through Garuda Indonesia. Future study was suggested to add other variable measurement and use population or sample to other companiesÂ Study